Head‐to‐Head Linkage Containing Bithiophene‐Based Polymeric Semiconductors for Highly Efficient Polymer Solar Cells. Issue 45 (22nd September 2016) - Shi, Shengbin; Liao, Qiaogan; Tang, Yumin; Guo, Han; Zhou, Xin; Wang, Yulun; Yang, Tingbin; Liang, Yongye; Cheng, Xing; Liu, Feng; Guo, Xugang
Abstract : Narrow bandgap (1.37–1.46 eV) polymers incorporating a head‐to‐head linkage containing 3‐alkoxy‐3′‐alkyl‐2, 2′‐bithiophene are synthesized. The head‐to‐head linkage enables polymers with sufficient solubility and the noncovalent sulfur–oxygen interaction affords polymers with high degree of backbone planarity and film ordering. When integrated into polymer solar cells, the polymers show a promising power conversion efficiency approaching 10%.